Life is in the transitions : mastering change at any age - Feiler, Bruce, 1964- (Penguin Press, 2020)
"Bruce Feiler has long been thinking and writing about the stories that give our lives meaning. Several years ago he began to notice a new pattern: the old stories about the major plot points of our lives were no longer holding true. Increasingly, he observed, the stories we all inherit to explain how our lives should unfold were clashing with reality and creating more anxiety than guidance. People felt they were living their lives out of the expected order and were beset by transitions at a faster and faster pace. Galvanized by a family crisis that spoke quite poignantly to this loss of meaning, Feiler set out on what became an epic journey to harvest American life stories and see what he could learn from them. What began organically, radiating out from family and friends, became more ambitious and rigorous, until he gathered 225 extended life stories from all 50 states in what he called The Life Story Project. As Bruce sifted through and coded the themes of his interviews, powerful and pressing patterns emerged. We are living our lives out of order--the midlife crisis, for one, thing, is a big myth. We do think of our lives as having a shape. The old linear model of life has been replaced by what he calls the nonlinear life. This nonlinear life involves being bombarded more life transitions. Feiler draws on an extraordinary well of insight from his interviewees and offers powerful new tools for navigating the growing number of life transitions we all face. His is a book that can move readers of any age and any life moment to think deeply about how their story serves them and how it can serve them better"--